Effect of Flux Composition on the Percentage Elongation and Tensile Strength of Welds in Submerged Arc Welding - Singh Brijpal; Khan Zahid A.; Siddiquee A.N.; Maheswari Sachin; Sharma Satish Kumar (Archive of Mechanical Engineering, 2016)
This experimental study reveals the effects of CaF2, FeMn and NiO additions to the base fluxes on tensile strength and percentage elongation of the weld metal. The aim of this study is to develop suitable flux for mild steel for high tensile strength, impact strength and ductility. Bead on plate welds were made using submerged arc welding process. Mathematical model for percentage elongation and UTS of mild steel welds were made. The elements transfer to the welds have been correlated with the above mechanical performance characteristics. The effect of oxygen content on weld elongation and UTS also has been deduced. This study shows that CaF2 and NiO are the significant factors for tensile strength while FeMn is not significant for tensile strength. However, for elongation besides CaF2, the interaction of CaF2 and FeMn was also found significant. The effects of basicity index of the flux and carbon equivalent of the welds on tensile strength and percentage elongation of the welds have also been evaluated.